Parasitism (Flamingolepis liguloides Gervais, 1847) with High Prevalence in Brine Shrimp Population from Çamaltı Saltworks - Edis Koru (Journal of Agricultural Sciences)
Populations of the species Artemia (Brine shrimp) in saltworks have become a popularity popular field of study for aquaculture for its significance for aquatic ecosystems as being an important source of sustenance for water birds in hypersaline food webs. Besides, species in the genus Artemia are the intermediate host of severe cestode species which are associated with flamingos. This study reports on the prevalence of native Artemia parthenogenetica parasitism of Flamingolepis liguloides in the Çamaltı saltern ecosystem in the Gediz wetland between January and December 2022 in Türkiye. Infected A. parthenogenetica was sampled from April to September 2022 in salt pans where flamingo birds and salt production are available for parasitological diagnosis. The parasites were determined in the abdomen, thorax and near the gut tract of A. parthenogenetica. The highest prevalence of parasite was found in juvenile individuals as 86.67±1.45% and adults as 76.06±1.16% in May. The main intensity was varied from 1.18±0.01 to 1.92±0.06 parasites per infected host depending on the sampling months and age of the brine shrimp. The most abundant parasite infestation was recorded as 1.44±0.02 parasites per investigated host in juvenile brine shrimp in June since seasonal conditions are favorable for such infestation.